The clinical diagnosis and treatment of phospholipase C zeta (PLCζ) deficiency and the development of a nanoparticle-mediated delivery method for sperm - Galal, S (2024)
Background: Sperm-specific phospholipase C zeta (PLCζ) triggers Ca2+ oscillations that activate oocytes in mammals. The regulatory mechanisms of PLCζ expression remain unknown. Sperm from patients with PLCζ deficiency or functional mutagenesis in the PLCZ1 gene are unable to activate oocytes. Although the only therapeutic option available for these patients is chemical assisted oocyte activation (AOA), many concerns regarding its safety limit its wider application. Using recombinant human phospholipase C zeta (rhPLCζ) for AOA is a safer option, but synthesising an active purified form and injecting it into the oocyte is challenging. Using HEK293T cell as a vector might provide the protein with necessary post-translation modifications, thus increasing protein solubility. Nanoparticles can also be used for the intra-gamete delivery of rhPLCζ, but safety and efficacy concerns need to be addressed. Solid silica nanoparticles (SSNPs) are known to be robust, versatile and non-toxic for many cell types; however, their delivery potential into mammalian gametes and biocompatibility are not deeply investigated. Moreover, the functionalisation of SSNPs using TAT-peptide (a cell-penetrating peptide known to facilitate nuclear targeting), may further enable the targeting of the nuclei of mammalian gametes, thus enabling gene studies, genetic manipulation and create the base for gene therapy in gametes aiming to improve the outcomes of ART. Aim of this thesis: The primary aims of this project were to enhance our ability to diagnose and treat PLCζ deficiency and to develop a nanocarrier that could act as a non-invasive delivery system to deliver various biomolecules into mammalian gametes. Materials and methods: This thesis involved the diagnosis of PLCζ deficiency in patients using an immunoassay with subsequent AOA recommendation and molecular analysis to identify mutations in the PLCZ1 gene and the promoter region. Assessment of PLCζ expression in sperm with abnormal morphology was conducted to understand the expression mechanisms of PLCζ. Then, SSNPs were synthesised, characterised to target the cytoplasm of mammalian gametes and functionalised with TAT-peptide to target the nuclei, followed by investigating their potential nanotoxicity and possible internalisation. Then, a rhPLCζ was synthesised using HEK293T cells, and the ability of this protein to activate the oocytes was investigated via in vitro incubation with oocytes and injection. Finally, the protein was loaded onto SSNPs and incubated with oocytes to investigate oocyte activation rate. Results: 68.18% of patients had significantly lower levels of PLCζ and/or lower proportions of sperm exhibiting PLCζ, thus, PLCζ immunoassay was an effective method to diagnose patients with PLCζ deficiency. Single nucleotide polymorphisms identified in the PLCZ1 gene and sperm morphology had no clear link with the expression of PLCζ. Exposure to various types of SSNPs did not affect key parameters of mammalian sperm function, including motility and apical ridge morphology (P>0.05) and had mild effect on the expression of key genes. Unmodified SSNPs spontaneously interacted with mammalian gametes and successfully targeted 40% of mammalian sperm nuclei using TAT-peptide. Incubation of oocytes with the rhPLCζ significantly induced oocyte activation compared to a control group (P<0.0001). SSNPs loaded with rhPLCζ induced rapid oocyte activation of 86% of incubated oocytes within one hour and subsequent degeneration while no activation was observed in the control groups of oocytes. Conclusion: Our in-house PLCζ immunoassay can effectively diagnose PLCζ deficiency. Using a mammalian vector to synthesise rhPLCζ resulted in an active protein capable of activating the oocytes by incubation without the need to inject the protein. SSNPs can be used for delivering biomolecules into the cytoplasm and nuclei of gametes. SSNPs were successful in delivering rhPLCζ into oocytes and inducing oocyte activation. While this rhPLCζ represents a highly potential candidate for AOA, further investigations are required to estimate the exact amount of protein that interacted with the oocytes and how to optimise the dose required for physiological oocyte activation. SSNPs show great promise for clinical application, it is crucial to conduct further research to fully investigate their potential long-term effects on gametes, including their persistence inside the gametes and possible associated risks.